Guided Growth Technique for Epiphysiodesis and Hemiepiphysiodesis: Safety and Performance Evaluation - Giovanni Luigi Di Gennaro; Giovanni Trisolino; Stefano Stallone; Marco Ramella; Gino Rocca; Giovanni Gallone (MDPI AG, 2023)
Background: Guided-growth modulation is a first-line treatment widely adopted to correct lower-limb angular deformities and limb-length discrepancies (LLD) in the paediatric population. Methods: We conducted a retrospective study to evaluate the safety and performance of a new construct (8-Plate Plus or Guided-Growth Plate System Plus, Orthofix S.r.l) used to correct angular deformities and LLD in non-skeletally mature children. The primary endpoint was safety (from plate implantation to removal). The secondary endpoint was performance; patients treated for LLD achieved complete correction if a pre- and post-surgery difference of <0 was observed; angular deformities performance was measured in terms of IMD, ICD, mMPTA, and mLDFA. Results: We performed 69 procedures in 41 patients. A total of 10 patients had an LLD, and 31 had an angular deformity. We observed nine minor complications in the hemiepiphysiodesis group. One patient experienced rebound. All 10 LLD patient treatments were successful. A total of 30/31 patients with an angular deformity had a successful treatment; the remaining patient had a partial correction. Conclusions: Guided-growth by temporary epiphysiodesis or hemiepiphysiodesis was safe and effective for angular deformities and limb-length discrepancies. Further prospective and/or randomized controlled trial studies assessing more significant cohorts of patients and a comparison group could add evidence to our findings.